Pemanfaatan Cladophora glomerata untuk menurunkan Zat Organic pada Limbah Laundry dengan Pencahayaan Artificial - aulia ulfah farahdiba (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2019)
Macroalgae is an alternative technology for reduce organic content in wastewater. This study develop the performance of Cladophora glomerata species as a Macroalgae to remove laundry wastewater pollutants with artificial light. Light exposure conducted in 12 hours and 24 hours exposure to the algal reactor with nutrient variance concentration. The results of this study showed that macroalgae succeeded in reducing organic matter as COD to ±25.81% and BOD to ±54% within in 5 days. Performance of algae to decrease organic substance determine the effect algal-bacteria symbiosis which prevail in the reactor. Furthermore, nutrient content could affect the algal ability to remove the organic substance